Silica-based ionogels containing imidazolium ionic liquids and their electrorheological responses at room and elevated temperatures. (September 2021) - Chen, Panpan; Zhao, Zhenjie; Zhang, Guangchen; Jin, Xiao; Wang, Li-Min; Liu, Ying Dan
Abstract: In this study, we report the electrorheological (ER) effects of silica-based ionogels containing imidazolium ionic liquids (ILs) when dispersed in silicone oil at different temperatures. The amount of IL agent used in the synthesis process of the silica-based ionogels by a sol-gel method significantly affected morphologies of the silica-based ionogels, resulting in particles with rough surface and agglomerations. This electric-field-tunable rheological properties of the ionogel-based ER fluids were closely related to the dosage of ILs used in the synthesis process. With a proper amount of IL, the ionogels of SiO2 -IL-0.5, SiO2 -IL-0.8 and SiO2 -IL-1.0 showed enhanced ER effects under steady shear flow with an applied electric field compared with pristine SiO2 ; however, excessive ILs in ionogel (SiO2 -IL-1.88) could reduce the ER effect of the ER fluid. More importantly, upon modification by IL, the SiO2 -IL-0.8 ionogel exerted the highest ER effect which was stable in the temperature range of 25−120 °C, showing good applicability at high temperature.